2016
DOI: 10.3390/app6050156
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-Coordinate Measurement Machine (CMM) for Large-Scale Dimensional Measurement of Micro-Slits

Abstract: This paper presents a micro-coordinate measuring machine (micro-CMM) for large-scale dimensional measurement of a micro-slit on a precision die coater by using a shear-mode micro-probe. A glass micro sphere with a nominal diameter of 52.3 µm was attached on one end of a tapered glass capillary tube as a probe tip ball. The micro-slit width of a slot die coater with a nominal slit width of 85 µm was measured by the micro-CMM. The probe tip was placed in the slit for the measurement. The effective working length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The parameters values (d, e, f, g) can be thus be found by solving the simultaneous equations from Equations (10)- (13).…”
Section: T/t Rotating Shaft Internal Diametermentioning
confidence: 99%
“…The coordinate-measuring-machine (CMM) is now being widely applied as part of workpiece inspection in the production line [13][14][15][16][17]. It can be used to measure the geometry of physical objects by sensing the discrete points on the object surface with a probe, including mechanical, optical, laser, and white light.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the advancement of automation in industry is to suit the variety of desired functionalities for all technical measurement processes in the bike quality check (QC) [1][2][3][4]. Coordinate-measuring machine (CMM) platform is mostly applied by a device that measures the physical geometry by sensing discrete points on the surface with a probe for the measurement object [5][6][7][8][9]. CMM offers two major advantages: (1) physical geometry measurement with high precision up to 0.001 mm.…”
Section: Introductionmentioning
confidence: 99%